KEANEKARAGAMAN JENIS CAPUNG DI KAWASAN KAMPUS UNIVERSITAS TANJUNGPURA PONTIANAK - Muktitama, Senja Rizky; Prayogo, Harri; Indrayani, Yulianti (Universitas Tanjungpura, 2018)
Dragonfly is an indicator to environment and ecosystem in a particular area. It is also known as a balancing predator to another insectsâ€™ population. Various types of dragonfly are affected by some factors such as habitat conditions and the foods. Various types of dragonfly can be found in swamland, rice fields, flooded area, and also some locations around Universitas Tanjungpura. This research aims to convey information about various types of dragonfly in the area of universitas tanjungpura and also to define the index of variety of dragonfly types (H), equalization index (e), domination index (D), and species similarity (IS). This research took two weeks of fieldwork by applying purposive sampling, which was started from 5th â€“ 15 th Â April, 2018. Where the researcher is free to down each location seen from the large number of dragonflies are found. Then each location specified each plot with a distance of 15 meters each point of view of forming a circle pattern diameter 30 meters. The researcher found that 16 type of dragonfly consist of 13 type categorized as Subordo Anisptera and 3 type categorized as Subordo Zygoptera. The 13 Subordo Anisoptera consist of 12 types in libellulidae family and 1 type in Gomphidae family. The other 3 Subordo Zygoptera are in the the categoryof Coenagrionidae. This research shows that the role of dragonfly as a bioindicator and the predator of particular environment. Ecologically, Universitas Tanjungpura is indicated to have deficient environment in terms of the population growth of dragonfly in ecological ecosystem.Keywords: Dragonfly Habitat, Insects, Universitas Tanjungpura